2018
DOI: 10.3390/ijgi7020069
|View full text |Cite
|
Sign up to set email alerts
|

Roughness Spectra Derived from Multi-Scale LiDAR Point Clouds of a Gravel Surface: A Comparison and Sensitivity Analysis

Abstract: The roughness spectrum (i.e., the power spectral density) is a derivative of digital terrain models (DTMs) that is used as a surface roughness descriptor in many geomorphological and physical models. Although light detection and ranging (LiDAR) has become one of the main data sources for DTM calculation, it is still unknown how roughness spectra are affected when calculated from different LiDAR point clouds, or when they are processed differently. In this paper, we used three different LiDAR point clouds of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Highly detailed and accurate digital elevation models (DEMs) can provide valuable insights into important topographic characteristics, such as terrain steepness and roughness [1]. Roughness in particular has proven to be an integral characteristic when discriminating geomorphological features, such as landslides [2].…”
Section: Introductionmentioning
confidence: 99%
“…Highly detailed and accurate digital elevation models (DEMs) can provide valuable insights into important topographic characteristics, such as terrain steepness and roughness [1]. Roughness in particular has proven to be an integral characteristic when discriminating geomorphological features, such as landslides [2].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in the leaf inclination angle distribution between different parts within a tree was observed, and a detailed tree structural analysis was conducted. We found that this method enables accurate and efficient leaf inclination angle distribution.A 3D scanner called lidar (light detection and ranging) provides highly accurate and dense 3D point measurements [15,16]. The lidar is very useful for the retrieval of plant structural parameters.…”
mentioning
confidence: 99%
“…A 3D scanner called lidar (light detection and ranging) provides highly accurate and dense 3D point measurements [15,16]. The lidar is very useful for the retrieval of plant structural parameters.…”
mentioning
confidence: 99%
“…Just as a flashlight makes a larger circle on a wall from a greater distance, laser scans produce larger footprints when the sensor is farther away from a target reflective surface. The combination of footprint size, distance from the target, and target reflectivity fundamentally constrains the spatial resolving capacity of any laser scanner (Lichti and Jamtsho 2006; Milenković et al 2018). Commercial TLS instruments produce footprint sizes in the 2–5 cm range at 100 m (Disney et al 2018), allowing them to resolve small stems and branches.…”
Section: Technical Considerations For Drone Remote Sensingmentioning
confidence: 99%